Measuring Trust in Higher Education Evaluation Systems: Methods and Indicators - Hakimova Gulnoza Abdulloyevna; Hakimova Mushtariybonu Hamid kizi (Review of Multidisciplinary Academic and Practice Studies, 2026)
Abstract Purpose: This study aims to systematically analyze methods for determining the level of trust in the evaluation of the higher education system and to substantiate their scientific foundations by conceptualizing trust as a measurable and analytically significant dimension of evaluation Research Methodology:. A mixed-methods approach was employed by integrating quantitative statistical indicators and qualitative sociological survey data from key stakeholders, including students, academic staff, parents, and employers. Data were analyzed using descriptive statistics and expert-based weighting to construct an integrated trust index Results: The results show that trust in higher education evaluation is influenced by both system performance and stakeholders’ perceptions of fairness, transparency, clarity, and relevance. Graduate employment rates and academic staff capacity were the strongest quantitative determinants, while transparency and clarity of evaluation procedures were the most influential qualitative factors. Qualitative indicators slightly outweighed quantitative ones in shaping overall trust Conclusions: The study concludes that an integrated evaluation framework combining quantitative and qualitative indicators provides a more comprehensive assessment of trust and enhances the social legitimacy of higher education evaluation systems Limitations: The study is limited by its cross-sectional design, limited sample size, reliance on expert weighting, and the use of self-reported data Contribution: This research contributes by proposing an integrated trust index that can support policymakers and institutions in improving transparency, stakeholder confidence, and the effectiveness of higher education evaluation